Predicting Outcome for Early Attention Training After Acquired Brain Injury - Bartfai, Aniko; Elg, Mattias; Schult, Marie-Louise; Markovic, Gabriela (Frontiers in Human Neuroscience, 2022)
Background The training of impaired attention after acquired brain injury is central for successful reintegration in daily living, social, and working life. Using statistical process control, we found different improvement trajectories following attention training in a group of relatively homogeneous patients early after acquired brain injury (ABI). Objective To examine the contribution of pre-injury factors and clinical characteristics to differences in outcome after early attention training. Materials and Methods Data collected in a clinical trial comparing systematic attention training (APT) with activity-based attention training (ABAT) early after brain injury were reanalyzed. Results Stroke patients (p = 0.004) with unifocal (p = 0.002) and right hemisphere lesions (p = 0.045), and those with higher mental flexibility (TMT 4) (p = 0.048) benefitted most from APT training. Cognitive reserve (p = 0.030) was associated with CHANGE and APT as the sole pre-injury factor. For TBI patients, there was no statistical difference between the two treatments. Conclusion Our study identifies indiscernible factors predicting improvement after early attention training. APT is beneficial for patients with right-hemispheric stroke in an early recovery phase. Knowledge of prognostic factors, including the level of attention deficit, diagnosis, and injury characteristics, is vital to maximizing the efficiency of resource allocation and the effectiveness of rehabilitative interventions to enhance outcomes following stroke and TBI.